Exploring the Implications of Philoxenia on Social Cohesion between South Africans and African Immigrants: Empirical Insights from African Immigrants in Nelspruit, South Africa - Maseng, Jonathan Oshupeng; Gabara, Gundo (E-Journal of Humanities, Art and Social Sciences (Online), 2025)
This paper explored the implications of the existence of philoxenia on Social Cohesion between South Africans and African immigrants. The researchers employed an exploratory research design, qualitative research methods, and in-depth interviews to solicit data. Interviews were conducted with 15 African immigrants over the age of 18, originating from various African nations and living in Nelspruit, South Africa. The participants represented a range of cultural backgrounds, demographics, sexual orientations, and gender identities. The findings underscored both opportunities and challenges in fostering a more inclusive society. Thus, the paper revealed that while philoxenia positively contributes to social cohesion by encouraging kindness, empathy, and mutual respect, helping African immigrants integrate into South African society, there are barriers such as cultural differences and lingering prejudices, along with structural challenges like xenophobia, which complicate the process of full integration of African immigrants. The researchers recommend that the government and other stakeholders must establish sustained efforts to overcome barriers like cultural differences and personal preferences between these two groups. This paper sheds light on the fact that, besides the general narrative of xenophobia in South Africa, there exists philoxenia, which positively contributes to social cohesion by encouraging kindness, empathy, and mutual respect, helping African immigrants integrate into South African society. Keywords: African Immigrants, Philoxenia, South Africans, Social Cohesion